Exploring Research Paradigms in Social Science: A Literature Review of Positivist, Interpretive, Critical and Postmodern Perspectives - Muhammad Faisal Arif; Syarifuddin; Syamsuddin; Aini Indrijawati (Science and Technology: Developments and Applications Vol. 8, 2025)
This paper provides an explanation and comparison of several research paradigms commonly used by researchers. Some researchers use research paradigms to view reality, and there are various choices in viewing reality, such as positivistic, interpretive, critical, and postmodern paradigms, referring to the views of several experts, such as Burrell and Morgan in their book Sociological Paradigms and Organisational Analysis and Chua’s research titled Radical Development in Accounting Thought. Some paradigms have different perspectives in viewing reality, such as positivism which considers reality as something real that exists "out there" and can be studied independently with prediction and control, whereas non-positivism posits social reality as something that is merely a label, name, or concept used to construct reality, and there is nothing real. This difference is clearly evident in the researchers’ perspectives on reality, both from ontology, epistemology, and methodology. With this writing, it is hoped that researchers can understand how reality is viewed in various dimensions (paradigms) and gain an understanding of the comparisons and how these paradigms work.